Bicondylar tibial plateau fracture dislocations with an intact anterolateral cortical rim: A surgical technique. Issue 3 (March 2023) - Crabtree, Reaves M.; Bergin, Patrick F.; Graves, Matthew L.; Yener, Ugur; Bhanat, Eldrin; Day, William A.; Spitler, Clay A.
Abstract: A displaced medial tibial plateau fracture with central and lateral impaction, but an intact anterolateral cortical rim, is an uncommon variant of bicondylar tibial plateau fracture that presents a number of challenges. Without a lateral metaphyseal fracture line to work through, it is challenging to address central and lateral impaction. Previously published techniques for addressing this fracture pattern describe an intra-articular osteotomy of the lateral plateau to aid visualization and reduction, or use a posterolateral approach to the proximal tibia with or without an osteotomy of the proximal fibula. This study presents a technique which utilizes standard dual incision approaches and does not involve an intra-articular osteotomy of the lateral tibial plateau or a posterolateral approach. A case series was conducted evaluating radiographic and functional outcomes of 8 patients.